2018
DOI: 10.17261/pressacademia.2018.836
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing asset of bubbles in the housing market with right-tailed unit root tests: the case of Turkey

Abstract: Purpose-Housing markets are linked to macroeconomic and financial stability. The creation of different financial instruments on residence, the presentation of residence as an assurance, the impact of residence prices on saving and consumption through the wealth effect are some of the housing market and general economic interactions. Developments in the residential sector must be carefully monitored for financial stability. The residential sector has usually played an important role in the global economy and fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 23 publications
1
7
1
Order By: Relevance
“…According to their analysis, there is no evidence to support the existence of a price bubble in the mentioned housing markets. In addition, Afsar and Dogan ( 2018 ) reached a similar finding for the 2010-2017 period. They implemented ADF and Generalized SADF tests using real housing price index and rent index data and concluded that there was not a price bubble in the Turkish housing market.…”
Section: Literature Reviewsupporting
confidence: 55%
“…According to their analysis, there is no evidence to support the existence of a price bubble in the mentioned housing markets. In addition, Afsar and Dogan ( 2018 ) reached a similar finding for the 2010-2017 period. They implemented ADF and Generalized SADF tests using real housing price index and rent index data and concluded that there was not a price bubble in the Turkish housing market.…”
Section: Literature Reviewsupporting
confidence: 55%
“…Studies investigating the price bubbles in housing markets using the GSADF test: Zeren and Erguzel (2015), Engsted et al (2016), Shi et al(2016), Escobari and Jafarinejad (2016), Coskun and Jadevicius (2017) Afsar and Dogan (2018), Evrim et al (2018), Hu and Oxley (2018), Iskenderoglu and Akdag (2019), Gokce and Guler (2020), Abioglu (2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study also found a significant evidence of a price bubble in the regional sense in the late 1980s. Afşar and Doğan (2018) carried the study that shows the presence of housing price bubble for Turkey by using the SADF and GSADF test method. Similarly, the study also found that there is a bubble in housing prices for the period of 2010–2017 in Turkey.…”
Section: Literature Reviewmentioning
confidence: 99%